Computational Design of Near-Infrared Fluorescent Organic Dyes Using an Accurate New Wave Function Approach - Berraud-Pache, Romain; Neese, Frank; Bistoni, Giovanni; Izsák, Róbert (The journal of physical chemistry letters, 2019)
The extensive research focusing on fluorescent organic dyes for bioimaging has made this in vivo method available for a diverse range of applications. One way to enhance this method is to tune the absorption and emission wavelengths of dyes to the near-infrared region where better light penetration and imaging resolution can be achieved. For this purpose, the well-known BODIPY dyes and their derivatives called aza-BODIPY have been the subject of extensive synthetic efforts. The interest in these systems stems from their excellent photophysical properties. Despite numerous studies, the rational design of near-infrared active dyes with desirable properties remains difficult. Here, we present a new wave function-based method for modeling excited states of large molecules, which has numerous theoretical advantages over the most commonly used electronic structure methods. This method is employed to suggest candidates for new dyes with the desired properties and to predict the absorption and fluorescence maxima and luminescence spectra of aza-BODIPY dyes with possible applications in fluorescence imaging.